SOSIALISASI DAN EDUKASI PERALATAN ELEKTROMEDIK BAGI SISWA SEKOLAH MENENGAH ATAS - Ulin Nuha ABA, M.Si, Muhammad; Muslihun; Mugiyanto; Haris Kuspranoto, Abdul; Ekma Nurani, Annisa; Rachmawati, Putri (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
Technological advancements in healthcare have increased the demand for professionals in biomedical engineering. However, high school students' understanding of this field remains limited. This community service activity aimed to introduce the Biomedical Engineering study program, medical equipment, and related career prospects to senior high school students. The activity was conducted at SMAN 1 Pegandon, Kendal Regency, using lectures, demonstrations, group discussions, simulations, and a pre-test–post-test design to assess knowledge improvement. The results showed a 105.4% increase in students' knowledge scores, and 80% of participants expressed interest in the field. Furthermore, 90% of students reported gaining new insights into non-clinical healthcare professions. Exposure to devices such as patient monitors, ECGs, and defibrillators enriched the students' learning experience. This program successfully enhanced students' medical technology literacy and interest in vocational education in biomedical engineering.